Utilization of the Zucker Diabetic Fatty (ZDF) Rat Model for Investigating Hypoglycemia-related Toxicities. (August 2015) - Tirmenstein, Mark; Horvath, Joseph; Graziano, Michael; Mangipudy, Raja; Dorr, Thomas; Colman, Karyn; Zinker, Bradley; Kirby, Mark; Cheng, Peter T. W.; Patrone, Laura; Kozlosky, John; Reilly, Timothy P.; et al.
Glucokinase (GK) catalyzes the initial step in glycolysis and is a key regulator of glucose homeostasis. Therefore, glucokinase activators (GKa) have potential benefit in treating type 2 diabetes. Administration of a Bristol-Myers Squibb GKa (BMS-820132) to healthy euglycemic Sprague-Dawley (SD) rats and beagle dogs in 1 mo toxicology studies resulted in marked and extended hypoglycemia with associated clinical signs of toxicity and degenerative histopathological changes in the stomach, sciatic nerve, myocardium, and skeletal muscles at exposures comparable to those expected at therapeutic clinical exposures. To investigate whether these adverse effects were secondary to exaggerated pharmacology (prolonged hypoglycemia), BMS-820132 was administered daily to male Zucker diabetic fatty (ZDF) rats for 1 mo. ZDF rats are markedly hyperglycemic and insulin resistant. BMS-820132 did not induce hypoglycemia, clinical signs of hypoglycemia, or any of the histopathologic adverse effects observed in the 1 mo toxicology studies at exposures that exceeded those observed in SD rats and dogs. This indicates that the toxicity observed in euglycemic animals was secondary to the exaggerated pharmacology of potent GK activation. This study indicates that ZDF rats, with conventional toxicity studies, are a useful disease model for testing antidiabetic agents and determining toxicities that are independent of prolonged hypoglycemia.